Between the 3rd and 2nd Millennia BC Exploring Cultural Diversity and Change in Late Prehistoric Communities - Lopes, Susana Soares; Gomes, Sérgio Alexandre (Archaeopress Publishing, 2021)
Between the 3rd and 2nd Millennia BC: Exploring Cultural Diversity and Change in Late Prehistoric Communities is a collection of studies on the cultural reconfigurations that occurred in western Europe between the 3rd and 2nd millennia BC. It brings together seven texts focusing on the evidence from the West of the Iberian Peninsula, and one on the South of England. The texts have their origin in a landmark meeting held at the University of Coimbra in November 2018, where scholars explored the grand narratives explaining the differences between what are traditionally considered Chalcolithic (or Late Neolithic) and Bronze Age communities. The contributions look at key aspects of these grand narratives through regional perspectives, asking the following questions: is there clear data to support the idea of an intensification of social complexity towards the emergence of the Bronze Age chiefdoms? What is the role of monumental architecture within this process? How do we best discuss the different levels of architectural visibility during this period? How can we interpret collective and individual burials in relation to the emergence of individual/territorial powers? In answering these questions, the papers explore regional diversity and argue that regional specificities resist a general interpretation of the historical process at stake. In light of this resistance, the book emphasizes that cultural singularities only become visible through contextual, medium, or low-scale approaches. The recognition of singularities challenges grand narratives, but also carries the potential to expand our understanding of the changes that occurred during this key moment of Late Prehistory. The book thus offers readers the opportunity to think about the diversity of archaeological evidence in combination with an exploration of the available range of approaches and narratives. The critical intertwining of multiple points of view is necessary, because it gets us closer to how elusive the cultural differences of prehistoric communities can be. This elusive dimension is precisely what can force us to constantly rethink what we see and what questions we ask.